NEIGHBORHOODS AND HUMAN DEVELOPMENT SOCI 473: Methods of Life-Course Research - Settersten, Richard (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This semester, we have often referenced one of the fundamental propositions of developmental science: that social contexts affect human development. Communities and, more specifically, neighborhoods are one of several central settings of everyday life, and they undoubtedly give the life course significant shape and meaning. In this project, you will work in groups and consider how neighborhoods affect human development.